024 Maximising efficiency in updating guidelines through prioritisation of clinical questions. (15th August 2013) - Amos, Q; Chan, W; Tom, G
Abstract : Background: To maximise efficiency in updating clinical guidelines it is important to understand which of its component clinical questions impact patient care most. Evaluating, editing, and prioritising of each clinical question is required to identify those that warrant updating. Objectives: To describe the methods used by a US health care delivery organisation to prioritise questions within an integrated cardiovascular guideline to determine those that were most important for updating. Methods: 127 clinical questions within an integrated cardiovascular guideline were ranked (using a Likert scale of 1–9) by importance for literature monitoring by clinical experts in each disease domain of the guideline. Examples of factors that influenced rankings included existence of high quality systematic reviews, knowledge that current evidence was relatively unchanged, and the notion that the question was no longer clinically relevant. Questions ranked 7–9 in importance for literature monitoring were considered most important for updating. Conversely, questions with low rankings were considered for retirement. Results: Of 127 questions ranked, 16 were identified as important for literature updating; 12 were retired. We were able to address the most important questions and avoid updating delays of 6–18 months. Discussion: Having these questions prioritised at the outset of updating allowed the healthcare organisation to ensure that the most important clinical questions were being addressed thus making the most efficient use of resources. Implications for Guideline Developers/Users: Evaluating, editing, and prioritising clinical questions improves efficiency when updating guidelines.